Numerical Investigation on Aerodynamic Characteristics of Bio-Inspired Nose Airfoil NACA 4415 - Fitri Wahyuni; James Julian; Saphira Anggraita Siswanto; Riki Hendra Purba; Fathin Muhammad Mahdhudhu; Elvi Armadani; Nely Toding Bunga (Fakultas Teknik Universitas Pancasila, 2026)
It is widely believed that bionic airfoils can influence aerodynamic performance. Therefore, this study focuses on analyzing the effect of a bio-inspired nose on the NACA 4415 airfoil. This study uses roughtoothed dolphins and spinner dolphins as modifications of the airfoil, which are then tested at Re = 1.6×105 using Computational Fluid Dynamics (CFD). From the simulation results, it was shown that the baseline NACA 4415 has the best aerodynamic performance across all Angles of Attack (AoA). The average percentage increase in Cd for the spinner dolphin is lower, at 40.399% compared to the baseline. On the other hand, the roughtoothed dolphin shows a higher percentage increase in Cd with an average of 51.479% compared to the baseline. While in the Cl data, the rough-toothed dolphin has a larger average percentage decrease, at -10.472%, whereas the spinner dolphin achieves an average decrease of only -5.194% compared to the baseline. Therefore, it can be concluded that the rough-toothed and spinner dolphin modifications do not enhance the aerodynamic performance of the NACA 4415 airfoil at AoA. However, at low AoA, the roughtoothed dolphin modification performs comparably to the baseline NACA 4415 airfoil.